2020
DOI: 10.3390/ijms21249550
|View full text |Cite
|
Sign up to set email alerts
|

Cellular, Extracellular and Extracellular Vesicular miRNA Profiles of Pre-Ovulatory Follicles Indicate Signaling Disturbances in Polycystic Ovaries

Abstract: Cell-free RNAs have the potential to act as a means of gene expression regulation between cells and are therefore used as diagnostic markers describing the state of tissue environment. The origin and functions of such RNAs in human ovarian follicle, the environment of oocyte maturation, are unclear. The current study investigates the difference in the microRNA profiles of fertile women and polycystic ovary syndrome (PCOS) patients in three compartments from the same preovulatory follicle: mural granulosa cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…The majority of these investigations have implied that progesterone in the FF is responsible for the enhancement of sperm function and induction of acrosome reaction [ 19 , 20 , 21 ]. Several recent studies have shown that FF contains extracellular vesicles (EVs) [ 22 , 23 ]. EVs are membrane-bound biological nanoparticles released by almost every cell type [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of these investigations have implied that progesterone in the FF is responsible for the enhancement of sperm function and induction of acrosome reaction [ 19 , 20 , 21 ]. Several recent studies have shown that FF contains extracellular vesicles (EVs) [ 22 , 23 ]. EVs are membrane-bound biological nanoparticles released by almost every cell type [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of literature that describes EVs as mediators of intercellular communication [ 25 , 26 ]. Recent studies have shown that FF EVs play a vital and supportive role in various reproductive processes such as cumulus expansion [ 27 ] and meiotic resumption of oocytes [ 28 ], ovarian physiology [ 23 ], modulation of the oviduct in preparation for fertilization and embryo development [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, this paper, representing the first study investigating miRNA profiles in FF from young women with HL, could be the starting point for further molecular studies exploring the quality of the follicular microenvironment, in order to improve counseling patients during the oncofertility protocol. A possible application could be to find biomarkers of oocyte competence in CC, GC or FF inside the single follicle, as well described in a recent publication (Rooda et al, 2020). In fact, we know that the retrieved oocytes from a single stimulation protocol do not necessarily have equivalent quality (Di Pietro et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs have been detected from all body fluids, including FF [32,56], and may be involved in cell-to-cell communication [33]. miRNAs can be secreted from cells as a part of RBPs or packed into EVs [33].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, hsa-mir-548 family members have been detected from other body fluids in addition to FF: hsa-miR-548b-5p, hsa-miR-548c-5p and hsa-miR-548i [57], and hsa-miR-548a-3p [58] in blood serum samples, hsa-miR-548b-3p in blood plasma, bronchial lavage and peritoneal fluid, and hsa-miR-548d-5p in amniotic fluid [59]. Some miRNAs infiltrate into the FF from blood plasma [32], explaining the lack of their expression in the granulosa cells. Additionally, the oocyte has not been investigated as the source of miR-NAs secreted into the FF due to the lack of such human data.…”
Section: Discussionmentioning
confidence: 99%